Islamic Contribution To Accounting - An’im Fattach; Mufidul Abror; Akhlis Priya Pambudy (Sean Institute, 2024)
The recent development of Islamic banks and financial institutions has created challenges for sharia and accounting experts. Experts are required to develop accounting standards that are different from the accounting standards applied by conventional financial institutions. Because in principle Islamic financial institutions are different from conventional financial institutions. This of course also has implications for the presentation of financial reports. Accounting as a science is needed to design financial reports which are actually needed by interested parties to make decisions regarding their activities. When the phrase Islamic accounting is expressed by experts, it must be justified by a clear concept and roots strong history. So the argumentative construct offered is difficult to refute. The Islamic accounting discourse was not born in a vacuum, but was stimulated by many factors that interacted in a complex, non-linear, dynamic and developing manner. Factors such as changing conditions in political, economic, social and cultural systems, increased religious awareness, revival spirit, scientific developments, all interact in a complex manner and ultimately give birth to the Islamic paradigm in the world of accounting.